2010
DOI: 10.1177/1090820x10383399
|View full text |Cite
|
Sign up to set email alerts
|

Improved Surgical Access for Facial Dimple Creation

Abstract: As an alternative to blind coring of the soft tissue from the buccal mucosa to the dermis or the placement of transcutaneous sutures, both of which can be associated with untoward side effects, the authors describe a safe and effective method for creating dimples through an open technique that replicates the anatomical basis of a natural dimple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…All the techniques described essentially have the same principle to create adhesion between the underlying muscular structures and the dermis, so that traction may create a dimple due to the dermal tethering effect. All the techniques described have claimed dimple creation surgery to be a very safe procedure with good results and a very low complication rate …”
Section: Dimple Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…All the techniques described essentially have the same principle to create adhesion between the underlying muscular structures and the dermis, so that traction may create a dimple due to the dermal tethering effect. All the techniques described have claimed dimple creation surgery to be a very safe procedure with good results and a very low complication rate …”
Section: Dimple Surgerymentioning
confidence: 99%
“…All the techniques described have claimed dimple creation surgery to be a very safe procedure with good results and a very low complication rate. [38][39][40][41] With refinement in surgical technique, there is an increasing demand for dimple creation surgery. In one center in Maharashtra (India), authors have reported creation of 100 dimples in the period 2006-2010.…”
Section: Dimple Surgerymentioning
confidence: 99%
“…Cheek dimples is always considered as an attractive facial feature in both males and females with no specific predominance (1,2) , they may occur unilateral or bilateral and usually are genetically inherited as a dominant trait (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Dimples are dynamic facial features, this means that they show up with facial animations and disappear upon rest. This is attributed anatomically to an abnormal insertion of the facial muscles to the skin (2) . Anatomical studies of the cadaveric faces showed that there is a variation of the zygomaticus major muscle that has bifid insertion, the inferior slip was found to be inserted into the dermis of the buccal chin and was attributed to the occurrence of the facial dimples as the skin is tethered to the contracting muscle (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation